Age at menarche in Seveso daughters exposed in utero to 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin. Issue 5 (24th October 2020) - Warner, Marcella; Rauch, Stephen; Ames, Jennifer; Mocarelli, Paolo; Brambilla, Paolo; Eskenazi, Brenda
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: In utero exposure to 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) is associated with delayed pubertal development in animal studies. No epidemiologic study has investigated this association. We examined the relationship of in utero exposure to TCDD with reported age at onset of menarche in female children born to a unique cohort of TCDD-exposed women resulting from an explosion in Seveso, Italy, on 10 July 1976. Methods: In 2014, nearly 40 years after the explosion, we enrolled postexplosion offspring, 2 to 39 years of age, in the Seveso Second Generation Study. Age at onset of menarche (years) was collected for 316 daughters by maternal report or self-report at interview. In utero TCDD exposure was defined by maternal TCDD serum concentrations extrapolated to the pregnancy. Results: At interview, 287 daughters were postmenarche and reported age at menarche averaged 12.1 years (±1.3 years). Overall, we found no change in risk of menarche onset with a 10-fold increase in in utero TCDD exposure (hazard ratio [HR] = 0.86; 95% confidence interval [CI] = 0.71, 1.04). When we considered maternal menarche status in 1976 as a potentially sensitive developmental exposure window, in utero TCDD (log10 ) was associated with later age at menarche among daughters whose mothers were premenarche (HR = 0.71; 95% CI = 0.52, 0.97) but not postmenarche (HR = 0.89; 95% CI = 0.71, 1.12) at the time of the explosion ( P int = 0.24). Conclusions: These results suggest that in utero TCDD exposure may alter pubertal timing among daughters of women who were prepubescent at the time of the Seveso accident.